Influence of Plasma-Activated Water on Physical and Physical–Chemical Soil Properties - Šimečková, Jana; Krčma, František; Klofáč, Daniel; Dostál, Lukáš; Kozáková, Zdenka (MDPI, 2020)
Recently, the bactericidal and fungicidal effects of plasma-activated water (PAW) have been confirmed for its application in agriculture. Although the PAW application is beneficial in plant growth, no information is available about processes induced by PAW in soil. This paper gives the first experimental results about PAW’s influence on selected physical and physical–chemical properties of soil. PAW was prepared using the dielectric barrier discharge (DBD) operating in the multistreamer mode at a frequency of 11 kHz. The total energy consumption was 60 J/ml. The obtained results show minimal changes in the natural water evaporation from the soil exposed to PAW, slower tap water absorption if a higher amount of PAW (16 doses per 10 ml to 90 g of the soil) is applied, as well as water retention in the soil of over 30%. The soil pH remains in the neutral range of values even at the highest applied PAW amount of 1.7 weight of soil, which represents the best conditions with respect to the plant growth. Thus, we can conclude that the PAW application, even at high amounts, has no negative influence on the physical and physical–chemical properties of soil and it can be safely applied in sustainable, environmentally friendly agriculture.

Recently, the bactericidal and fungicidal effects of plasma-activated water (PAW) have been confirmed for its application in agriculture. Although the PAW application is beneficial in plant growth, no information is available about processes induced by PAW in soil. This paper gives the first experimental results about PAW’s influence on selected physical and physical–chemical properties of soil. PAW was prepared using the dielectric barrier discharge (DBD) operating in the multistreamer mode at a frequency of 11 kHz. The total energy consumption was 60 J/ml. The obtained results show minimal changes in the natural water evaporation from the soil exposed to PAW, slower tap water absorption if a higher amount of PAW (16 doses per 10 ml to 90 g of the soil) is applied, as well as water retention in the soil of over 30%. The soil pH remains in the neutral range of values even at the highest applied PAW amount of 1.7 weight of soil, which represents the best conditions with respect to the plant growth. Thus, we can conclude that the PAW application, even at high amounts, has no negative influence on the physical and physical–chemical properties of soil and it can be safely applied in sustainable, environmentally friendly agriculture.
Influence of Plasma-Activated Water on Physical and Physical–Chemical Soil Properties
Keywords: plasma-activated water; dielectric barrier discharge; reactive oxygen species; reactive nitrogen species; soil pH; water retention; water absorption; plasma agriculture; plasma-activated water; dielectric barrier discharge; reactive oxygen species; reactive nitrogen species; soil pH; water retention; water absorption; plasma agriculture